Strengthening the Role of Cadres with Digital Literacy in iPosyandu Application-Based Recording and Reporting - Susanti, Ari Indra; Nuraini, Annisa; Ferdian, Dani; Nurparidah, Rani; Jayanti, Evi Dwi (Universitas Padjadjaran, 2023)
Posyandu is part of the Community-Sourced Health Efforts (UKBM), a health information system in maternal and child health services. Currently, health recording and reporting are still in paper form. Therefore, an iPosyandu application facilitates and accelerates cadres in recording and reporting. This activity was carried out in March 2023 to 145 cadres in Pagedangan District, Tangerang Regency, Banten. The method used was training on recording and reporting based on the iPosyandu application, where cadres were given a questionnaire on the use of the iPosyandu application. The results of this activity showed that most of the cadres had the characteristics of age 31-40 years (41.4%), the last education was high school (55.2%), the occupation was taking care of the household (97.9%), and the experience of being a cadre for 1-5 years (51%), and most of the cadres serving in the posyandu had middle strata (41%). Most cadres agreed to use the iPosyandu application because it can make reports quickly (83.7%), and cadres felt that the iPosyandu application had all the functions based on cadres' abilities (87.1%). In addition, there is a relationship between the last education of cadres and the use of iPosyandu applications (p-value < 0.005; r value > 1). This community service activity concludes that cadres have good digital literacy in using the iPosyandu application, so the system for recording and reporting the results of posyandu activities can run well. Keywords: iPosyandu, cadres, digital literacy, recording, reporting.